Association of Placental Umbilical Cord Insertion Site with Maternal and Fetal Outcomes: A Prospective Study - Sabu, Brinda; Hakkim, Sameera; Ambat, Roshini (Journal of Fetal Medicine, 2024)
Introduction Adequate fetal growth during pregnancy depends upon the normal development and insertion of the umbilical cord. Central/paracentral placental cord insertion is considered normal, while marginal/velamentous cord insertion is considered abnormal. Although the location of placental umbilical cord insertion can be determined by ultrasound (US), it is not included in the routine protocol of a targeted anomaly scan. Through this study, we determined different placental umbilical cord insertion sites by US and categorized them as normal and abnormal, identified the risk factors involved, and evaluated the outcome of pregnancies using standard protocols. The rationale of this study was to identify pregnancies that require frequent monitoring and surveillance for an optimal perinatal outcome.Methods A prospective cohort study was conducted in a tertiary care hospital for 18 months. A total of 345 pregnant women who attended the antenatal outpatient department between 18 and 22 weeks for targeted imaging for fetal anomalies scan were included in the study after informed consent. Detailed history followed by US documentation of the cord insertion site on the placenta was done and women were followed up throughout pregnancy to look for development of complications including hypertensive disorders, antepartum hemorrhage (APH), and fetal growth restriction (FGR). Intrapartum adverse events like fetal distress and intrapartum hemorrhage were assessed. Confirmation of US findings was done by macroscopic examination of the placenta and measuring the distance between the placental cord insertion and the edge of the placenta. The weight of the placenta was also documented. Newborns were evaluated for adverse outcomes like preterm birth, low birth weight, need for resuscitation, and neonatal intensive care unit (NICU) admission. Follow up of neonates and mothers was done till discharge.Results Placental cord insertion was accurately determined at the anomaly scan with 100% sensitivity and specificity. The study showed 44 abnormal placental cord insertions (ACIs)—42 had marginal and 2 had velamentous cord insertions. There was a high incidence of ACI noted in women aged more than 28 years, with body mass index of more than 26.38, multiparity, previous history of myomectomy, first trimester miscarriage, and conceived by assisted reproductive technology. Women with ACI had an increased risk of small for gestational age/FGR and APH and had an average baby weight of 2.7 kg, which was 200 g less than babies with normal cord insertion. They also had lower mean Apgar scores at 5 minutes and required resuscitation and NICU admission.Conclusion Our study concluded that it will be a good practice to document the placental cord insertion during the mid trimester anomaly scan so that we can identify the subset of pregnant women who are prone to develop complications, thereby providing adequate surveillance for an optimal perinatal outcome.
Keywords: marginal umbilical cord insertion; maternal outcome; fetal outcome; fetal growth restriction; baby weight